(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
This article focuses on the topic of stroke in neurology, specifically examining the pathophysiology, risk factors, clinical manifestations, diagnostic methods, and treatment options for stroke. The paper highlights the importance of early recognition and intervention to improve patient outcomes. It also explores the role of rehabilitation and post-stroke care in enhancing recovery and preventing complications. The article aims to provide a comprehensive overview for both healthcare professionals and patients to better understand the complexities of stroke and the importance of timely medical intervention.